Pengaruh Hasil Larutan Fermentasi Daun Gamal terhadap Pertumbuhan, Produktivitas dan Kualitas pada Tanaman Kale Curly (Brassica oleracea var. sabellica) - Edy Prasetya Sembiring; Nugraheni Widyawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to determine the effect of giving gamal leaf ferment solution on the growth, productivity and quality of kale plants and to obtain the concentration of gamal leaf ferment solution which has an optimum effect on the growth, productivity and quality of curly kale plants. The research method used in this study is the experimental method. The results showed that based on the results of the test of variance, liquid organic fertilizer (POC) fermented gamal leaves with concentrations of 0%, 40 ml/l, 80 ml/l, 120 ml/l and 180 ml/l had a very significant effect on plant growth. kale curly seen from plant height, number of leaves, stem diameter, and crown width, then related to the effect of giving gamal leaf ferment solution on the productivity of Kale Curly plants shows that there is a very significant effect on the parameters of root wet weight and root dry weight for each concentration given , whereas for the parameters of shoot wet weight and shoot dry weight did not show a significant effect, then on the quality of kale curly plants showed that there was a very significant treatment of POC fermented gagal leaves on total chlorophyll, but not significantly different for chlorophyll A, chlorophyll B, and vitamin C. So that it can be concluded that in this study the administration of fermented gamal leaves had a very significant effect on the growth of kale culy plants, for productivity there was a very significant effect on the parameters of root wet weight and root dry weight, but not with shoot wet weight and shoot dry weight , while for the quality of kale curly there was a very significant treatment for total chlorophyll, but not for chlorophyll A, chlorophyll B, and vitamin C, while the most optimum concentration of fermented galam leaves for growth, productivity, and quality of kale curly was administration of fermented gamal leaves with a concentration of 120 ml/l. Keywords: Gamal Leaves Fermentation, Quality, Growth, Productivity, Curly Kale Plant